Economic geography and the long-run effects of the Great Irish Famine - Whelan, Karl (Economic & Social Studies, 1999)
One of the most important debates in Irish economic history has concerned the long-run effects of the Great Irish Famine, with some arguing that it had only temporary effects on the economy and others seeing it as a major demographic and economic watershed. This paper adapts the theoretical framework of Krugman (1991) to illustrate how the combination of the Famine and developments in transportation and the demand for industrial products may have worked together to cause persistent depopulation and relative industrial decline.
Keywords: Economic geography; Economic history; Ireland; Famine